The effect of hydroxyapatite concentration on the mechanical properties and degradation rate of biocomposite for biomedical applications - D. F., Fitriyana; F. W., Nugraha; M. B., Laroybafih; R., Ismail; A. P., Bayuseno; R. C., Muhamadin; M. B., Ramadan; A. R. A., Qudus; J. P., Siregar (IOP Publishing Ltd, 2022)
Biocomposite is a material that have potential to heal injured bones and teeth due to their biocompatible, non-toxic, non-inflammation, and bioactive properties which can prevent infections that occurs frequently during surgical processes. Biocomposites made of PLA, PCL, and HA from bovine bone as a substitute for metal materials in medical applications have been widely studied. However, there are limited studies on the biocomposites made of PLA, PCL, and HA from green mussel shells. Therefore, this study aims to produce biocomposites from Polylactic Acid (PLA), Polycaprolactone (PCL), and Hydroxyapatite (HA) from green mussel shells and to determine the effect of HA concentration on the mechanical properties and degradation rate of the resulting biocomposite. 80 ml of chloroform was used to dissolve 16 grams of a PLA/PCL mixture with a composition of 80% and 20%. After 30 minutes, the solution was agitated for 30 minutes with a magnetic stirrer at 50°C and 300 rpm. After obtaining a homogenous solution, hydroxyapatite was added in percentages of 5%, 10%, 15%, and 20% of the total weight of the PLA/PCL mixture. The resulting mixture is poured into a glass mold in accordance with ASTM D790. Three-point bending, density, and biodegradable test were performed to investigate the effect of HA content on the mechanical properties and degradation rate of the biocomposite. The results of this study indicate that the mechanical properties of the biocomposite improved with the HA concentration increases. However, the more HA content used, the faster the biocomposite degrades.